Quantitative Approach to Circular Economy in the OECD Countries - Cristina Căutișanu; Laura Asandului; Mioara Borza; Ciprian Turturean (Amfiteatru Economic)
The circular economy, an evolving concept, is considered a necessary and pragmatic solution for reconciling the link between the growth rate and the pressure on the resources of the environment. Therefore, the purpose of the paper is the quantitative assessment of the circular economy in the OECD countries based on the indicators assembled by the authors. The goal set was achieved through both a theoretical and empirical objective. The theoretical objective is to combine and group indicators referring to the circular economy, as they are present in the literature. The empirical objective is to develop a model of causal analysis with significance for circular economy practice, based on indicators that measure economic growth, research-development, education, recycling. To achieve the empirical objective, cluster analysis, correlation analysis and path analysis were applied. The authors’ contribution consists of adapting circular economy indicators to the 5 newly created classes and applying the statistical methods mentioned in the OECD circular economy analysis. The results of empirical research reflect, on the one hand, the classification of countries for a set of indicators of the circular economy and the significant links and dependencies between the indicators analysed on the other.